1998
DOI: 10.1046/j.1464-410x.1998.00615.x
|View full text |Cite
|
Sign up to set email alerts
|

British urological surgery practice: 2. Renal, bladder

Abstract: Objective  To investigate the management of urological malignancies in the United Kingdom. Methods  A postal survey of consultant urologists and general surgeons with an interest in urology was conducted to examine current clinical practice in urological malignancies. Results  Completed questionnaires were received from 273 consultant surgeons who saw an estimated total of 13 241 new patients with renal, bladder or testis cancer per year; 82% had access to on‐site oncology services and in general there was a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…A study in the United Kingdom found that only 54% of urologists there routinely offered sperm banking before orchiectomy. 18 Most studies have recommended sperm banking before adjuvant therapy (chemotherapy or radiation), as these treatments have been shown to be associated with severe semen abnormalities. 4,5 The sperm retrieved can be used in different assisted reproductive methods for fertility with a high chance of success (pregnancy rate up to 30% per egg collection 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…A study in the United Kingdom found that only 54% of urologists there routinely offered sperm banking before orchiectomy. 18 Most studies have recommended sperm banking before adjuvant therapy (chemotherapy or radiation), as these treatments have been shown to be associated with severe semen abnormalities. 4,5 The sperm retrieved can be used in different assisted reproductive methods for fertility with a high chance of success (pregnancy rate up to 30% per egg collection 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Two thirds of UK urologists who responded to this survey are now doing radical cystectomy for muscle invasive bladder cancer themselves and others refer suitable patients to colleagues for this treatment modality. This is a major shift from previous practice when radiotherapy was favoured [1]. There has recently been emerging reports of a resurgence in bladder preserving treatments with chemo-radiotherapy after trans-urethral resection of tumour but it is too early to tell if this will gather momentum and more importantly, be sustained [11].…”
Section: Discussionmentioning
confidence: 99%
“…The latter is treated by either radical cystectomy by most urologists around the world when the disease is organ-confined and no co-morbidities exist or by radiotherapy when the patient either chooses this modality of treatment, disease is not organconfined or significant co-morbidities preclude major surgical intervention. In the United Kingdom, radiotherapy was the favoured way of treatment for muscle invasive bladder cancer [1]. However, over the last 10 years there appears to have been a gradual shift from this approach in favour of radical cystectomy.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of testis cancer is increasing [ 1] but there is still no universal agreement for the management of stage 1 disease. A recent survey of urology consultants [ 2] revealed that 67% would treat clinical stage 1 (CS1) seminoma by radiotherapy, 25% by observation and 7% by chemotherapy, and that 60% would chose observation for CS1 teratoma, 35% chemotherapy and 5% radiotherapy. These data do not reflect practice, as most patients after orchidectomy are managed by oncologists, but it does highlight the differing opinions amongst urologists.…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of The incidence of testis cancer is increasing [1] but there is still no universal agreement for the management of eCective salvage treatment for recurrent disease, all CS1 testis tumours received adjuvant treatment after orchi-stage 1 disease. A recent survey of urology consultants [2] revealed that 67% would treat clinical stage 1 (CS1) dectomy, i.e. modest doses of radiotherapy for seminomas and either radiotherapy or retroperitoneal lymph node seminoma by radiotherapy, 25% by observation and 7% by chemotherapy, and that 60% would chose obser-dissection (RPLND) for teratomas.…”
Section: Introductionmentioning
confidence: 99%